AQbD-Assisted Development and Validation of RP-HPLC Method for Simultaneous Quantification of Remogliflozin Etabonate, Vildagliptin, and Metformin Hydrochloride in Single Formulation - Jigar A. Shah, Dr. B.N. Suhagia (South Eastern European Journal of Public Health, 2025)
Introduction: The study aimed to optimize and validate a Reverse Phase High-Performance Liquid Chromatography (RP-HPLC) method for the simultaneous quantification of Remogliflozin Etabonate (REM), Vildagliptin (VIL), and Metformin Hydrochloride (MET) in a single pharmaceutical formulation. An Analytical Quality by Design (AQbD) approach was applied to ensure method robustness and reliability. Objectives: The study aimed to identify critical parameters influencing chromatographic separation, optimize method conditions using a Box-Behnken Design (BBD), and validate the RP-HPLC method in terms of retention time, linearity, and predictive accuracy. Methods: A risk estimate matrix was used to identify critical parameters, including acetonitrile quantity, pH, and flow rate. BBD was employed to assess their impact, and multiple linear regression models were developed to understand variable relationships. Chromatographic separation was performed using a Phenyl column at 25°C, with UV detection at 210 nm and 230 nm. The Method Operable Design Region (MODR) was determined to optimize conditions, and method validation included evaluating linearity and retention times. Results: The optimized method achieved efficient separation, with retention times of 4.5, 8.5, and 15.5 minutes for Vildagliptin, Remogliflozin Etabonate, and Metformin Hydrochloride, respectively. Linearity was established for Vildagliptin (1.25–37.5 μg/mL), Remogliflozin Etabonate (2.5–75 μg/mL), and Metformin Hydrochloride (25–750 μg/mL). Conclusions: The AQbD-based RP-HPLC method was successfully optimized and validated, ensuring accurate, reliable, and efficient simultaneous quantification of the three analytes in pharmaceutical formulations.